Pengembangan Video Pembelajaran Dengan Aplikasi Power Director Pada Tema 8 untuk Siswa Kelas V Sekolah Dasar - Putri, Intan Aprilia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This learning video development research uses a 4-D model. This model has four stages of development, namely Define, Design, Development, and Disseminate. This research was carried out until the develop stage, namely the validity test and practicality test. This validity test was tested by a validator of 3 lecturers, while the practicality test was assessed by 3 teachers and 71 students of grade V Elementary School. Test the validity and practicality of using a questionnaire as an instrument for data collection. Qualitative data is obtained from suggestions or improvements provided by the validator. Meanwhile, quantitative data was obtained from the results of a questionnaire using a Likert scale of 1-4. The results of the validity test of the Learning Video from material expert lecturers, media experts and language experts are very valid with a percentage of 91.66%. The practicality test results by the teacher are very practical, namely 90.83% and the practicality test results by students are very practical, 93.4%. From the results of this study, it can be concluded that the learning videos are very valid and very practical so learning videos can be used in the learning process in class V elementary school.